Power Usage Monitoring and Overload Protection System for Distribution Transformers - M. Syahruddin; Abdullah; Haq, Moh. Zainul; Putri, Maharani; Indah, Sarah Karima; Azhari, Syahdika Kurnia; Fiki, Akbar; Cholish; Roji, Fahrul (MultiTech Publisher, 2024)
Efficient energy manitoring and overload protection on distribution transformers are very much needed. This study aims to develop a power usage management system and overload protection integrated with Internet of Things (IoT) technology, with a specific target to monitor and manage power usage on distribution transformers in real time, as well as provide automatic protection against overload conditions. The methodology used in this study involves the design and implementation of hardware and software that supports wireless communication and data analysis. This system is also equipped with a power reading and protection mechanism that can automatically cut off the electricity flow when an overload detection occurs, in order to prevent damage to the transformer, it is expected that this system can increase the efficiency of power usage management and provide a quick response to overload conditions. The implementation of this system is expected to reduce operational costs and increase the reliability of electricity supply on the distribution network. Based on the tests that have been carried out, it has been proven that the system has worked well in maintaining important variables in the power usage management system and overload protection on the Internet of Things integrated distribution transformer.